Multislice computed tomography of pulmonary embolism - Bešlić, Šerif (Radiology and oncology (Ljubljana), 2005)
Background. The purpose of this study is to analyse the contribution of multislice computed tomography (MSCT) as a diagnostic method in the diagnosis of pulmonary embolism (PE) and spectrum of findings in our material. Methods. During the period of one and a half year, we found PE in 25 patients (15 malesand 10 females). The average age of the patients was 54.4 years (25 - 74). The examination was performed by Somatom Volume Zoom Siemens CT machinewith four row detectors, with retrospective ECG gating, collimation 4 x2.5 mm and reconstructed section with 0.8 mm. Contrast medium (130 ml) and 10ml of saline was applied, administered with a flow rate of 3.5 ml/s and withtime delay of 22 seconds. Results. During the examination, we found embolism of the main branches of pulmonary artery in 14 (56%) patients, at theright branch in 10 (40%), at the left one in 4 (16%), and bilateral pulmonary embolism in 11 (44%) patients. Subsegmental pulmonary emboli were noticed in 8 (32%) patients. Pulmonary infarct was found in 12 (48%) patients,and was followed up with ipsilateral pulmonary artery dilatation in 11 (44%) cases, redistribution of the circulation and pulmonary artery branches dilatation in infarct zone in 9 (36%) cases, contrast enhanced consolidation of pulmonary parenchyma in 10 (40%), rag zones of ground glass attenuation in 15 (60%), haemorrhage in 21 (84%), striped and reticular pulmonary drawing in 11(44%), and mosaic olighemy in 3 (12%) cases. (Abstract truncated at 2000 characters)
Keywords: Diagnosis; diagnostika; Pljučna embolija; pljučne bolezni; Pulmonary Embolism; računalniška tomografija; Tomografija radiografska, računalniška; Tomography, X-Ray Computed